Tone Reduction and Physical Therapy: Strengthening Partners in Treatment of Children with Spastic Cerebral Palsy - Franki, Inge; Bar-On, Lynn; Molenaers, Guy; Van Campenhout, Anja; Craenen, Karen; Desloovere, Kaat; Feys, Hilde; Pauwels, Petra; De Cat, Jos; Ortibus, Els (Neuropediatrics, 2020)
The aim of this paper is to provide a clinically applicable overview of different tone reducing modalities and how these can interact with or augment concurrent physical therapy (PT). Botulinum toxin (BoNT), oral tone-regulating medication, intrathecal baclofen (ITB), and selective dorsal rhizotomy are discussed within a physiotherapeutic context and in view of current scientific evidence. We propose clinical reasoning strategies to identify treatment goals as well as the appropriate and corresponding treatment interventions. Instrumented measurement of spasticity, standardized clinical assessment, and 3D clinical motion analysis are scientifically sound tools to help select the appropriate treatment and, when needed, to selectively target or spare individual muscles. In addition, particular attention is given to strength training as a necessary tool to tackle muscle weakness associated with specific modalities of tone reduction. More research is needed to methodologically assess the long-term effectiveness of such individualized tone treatment, optimize parameters such as medication dosage, and gain more insight into the kind of PT techniques that are essential in conjunction with tone reduction.
Keywords: cerebral palsy; tone reduction; spasticity; physical therapy